Bearing capacity of fiber reinforced soil - Wan Nuratiqah Ilyani, Wan Yusoff (2012)
During previous era, earth reinforcement is one of the method used that proven effective and reliable method to increase the strength and stability of soils. As an effective way for the soil stabilization, the technique is used today in a variety of applications ranging from retaining structures and embankments to subgrade stabilization beneath footings and pavements. Nowadays, randomly distributed fiber reinforced soils have attracted increasing attention in geotechnical engineering. A series of California Bearing Ratio (CBR) Test were done in this study. River sand and wire mesh fiber was selected as material for this testing. There are various laboratories testing for determination of soil classification that take place before CBR testing. For the sample preparation, 1 mm diameter of wire mesh fiber was cut in a range of 0.5-1 cm length. Different percentage of fibers that used for the testing are included 1 %, 3%, and 5%. Fibers were mix homogeneously with fine sand. In the current study, optimum moisture content (10%), +2% of moisture content (8.5%), and -2% of moisture content (11.24%) were used as control moisture for the testing. Optimum moisture content was developed from Standard Proctor Compaction Test. Results indicates that the CBR value increases with increasing percentage of fiber. For the reinforced soil, the results show that it is higher in CBR value compared to unreinforced soil. Besides that, according to bearing capacity of fiber reinforced soil in the CBR value, the optimum value of fiber content is 3%. The addition of 3% fiber shows the most obvious of the increases value of CBR. Inclusion of further higher fiber content will not provide the soil more strength than optimum value. In addition, sample with optimum moisture content (10%) shows the greatest gain. Very high moisture content will reduce the strength of the soil. In order to improve the result, the other test for determining of bearing capacity can be done such as plate load test which is require big scale test. Small scale size of the CBR test apparatus limits the amount of the fiber inclusion.